Study of 3D Printing and its Application - Chandra, Thalesh Anand; Patel, Mili; Singh, Prateek Kumar (International Journal For Research In Advanced Computer Science And Engineering, 2016)
This is a research paper on 3D printing which has become a notable topic in today’s technological discussion. In this paper, we will look at additive manufacturing or 3D printing. In this paper, we will look at additive manufacturing or 3D printing. We will firstly define what we mean by this term and what is so significant about it. We will delve a bit into the history. Then we shall see about the process of 3D printing and the materials used in the manufacture of 3D printed objects. We shall also see the advantages of 3D printing as compared to conventional methods of manufacturing. We shall observe the numerous applications it is being out to use today We will firstly define what we mean by this term and what is so significant about it. We will delve a bit into the history. Then we shall see about the process of 3D printing and the materials used in the manufacture of 3D printed objects. We shall also see the advantages of 3D printing as compared to conventional methods of manufacturing. We shall observe the numerous applications it is being out to use today. Finally the future potential of this technology is outline Introduction - 3D printing is a form of additive manufacturing technology where a three dimensional object is created by laying down successive layers of material. It is also known as rapid prototyping, is a mechanized method whereby 3D objects are quickly made on a reasonably sized machine connected to a computer containing blueprints for the object. The 3D printing concept of custom manufacturing is exciting to nearly everyone. This revolutionary method for creating 3D models with the use of inkjet technology saves time and cost by eliminating the need to design; print and glue together separate model parts. Now, you can create a complete model in a single process using 3D printing.